Synchronous double primary hepatocellular carcinoma and intrahepatic cholangiocarcinoma in a single patient with chronic hepatitis B: two case reports and literature review - Wei, Pengcheng; Kang, Nan; Lo, Chen; Luo, Yongjing; Gao, Jie; Zhu, Jiye; Li, Zhao (Frontiers in Oncology, 2025)
Simultaneous occurrence of primary hepatocellular carcinoma (HCC) and intrahepatic cholangiocarcinoma (ICC) is rare. We report two cases of synchronous double primary HCC and ICC (sdpHCC-ICC), both associated with chronic hepatitis B. Case 1 involves a 63-year-old man whose liver lesions were incidentally found during routine screening. Preoperative imaging revealed lesions in the S4 and S5 liver segments, with postoperative confirmation of sdpHCC-ICC. He received hepatic arterial infusion chemotherapy (HAIC) and transcatheter arterial chemoembolization (TACE) combined with gemcitabine and oral S-1 over 26 months, with no recurrence observed. Case 2 describes a 48-year-old woman presenting with right upper abdominal pain. Preoperative imaging identified a lesion at the S6/7 and S8 junction, later confirmed as sdpHCC-ICC. Postoperative TACE was performed at 1.5 and 3 months, and lenvatinib was introduced at 3.5 months. She remained recurrence-free at the 21-month follow-up. While the precise pathogenesis of sdpHCC-ICC remains unclear, chronic HBV infection plays a pivotal role. Surgical resection remains the primary treatment, though prognosis is generally poor due to the ICC component.